A Qualitative Research Study Exploring How the Coinciding Names of the Coronavirus And Corona Beer Has Affected Consumer Perceptions of Brand Equity - Thela, Phumelele (The IIE, 2022)
Brand equity has grown increasingly vital as a result of the global market's rapid changes and greater competition. Many brands prioritize the development of strong brand equity, but achieving this goal is not always easy owing to unforeseen crises. The following qualitative research study explores the influence of the Coronavirus name on Corona Beer’s brand equity amongst South African beer consumers. The research was guided by Aaker Brand Equity theory which holds that well-established and valued brands are more successful. The research was then informed by previous literature that focused specifically on brand crises, brand equity, and consumer perceptions of brand equity. The research methodology was then outlined and followed an interpretivist paradigm that focused on an exploratory research approach which aligns with the qualitative nature of the study. Data was collected through the use of a semi-structured interview with pre-drafted questions and analysed through the means of thematic content analysis. The findings of this research paper posits that companies can't predict a crisis, but they can develop a positive brand relationship that serves as a foundation of trust to counter against any possible threats in the marketplace.
Keywords: Buying patterns; Alcohol; Consumer behaviour; Brand value